Undergraduate University of the Philippines Diliman BLIS students' perceptions of the advantages and disadvantages of implementing an electronic security system at the ILIS Library - Irinco, Reila Anasol R. (2005)
This study, in improvising the security at the library of ILIS, attempted to determine if there is a need to install an electronic security system and the perceived advantages and disadvantages of installing an electronic security system in the library. This research used a survey questionnaire as a means to gather data. The researcher used Slovin's Formula to determine the sample size of the population. Two hundred nineteen (219) out of four hundred eighty eight (488) answered the questionnaire and these are undergraduate UP Diliman BLIS students.